„Człowiek jest czemś, co przezwyciężone być powinno”. Dyskurs historiozoficzny 2001: Odysei kosmicznej - Klejsa, Konrad (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
Drawing upon classic works on Kubrick’s 2001, the author ponders various strategies of interpretation which have been adopted to decipher the film’s discourse. The title category of historiosophy indicates one of the possible interpretational paths: the one associated with the Nietzschean notion of humankind stuck in a liminal stage between an animal and the overman. The author claims that such an understanding was typical of the late 1960s, and he pursues his argument with a close analysis of several sequences from the film, focusing on the formal devices which present the human protagonists as weak and lackluster, while the animal, the technological and the extraterrestrial characters are depicted as vital and irrepressible.